Pengaruh Konten Instagram Tas Visval Terhadap Keputusan Pembelian (Survei pada Followers Instagram @Visval) - Intan Sari; Velda Ardia (STIKes Ibnu Sina Ajibarang, 2025)
The fashion world greatly influences the lifestyle of Indonesian people, because people are more interested in paying attention to the appearance they wear. One of the fashion products that is currently developing in Indonesia is Visval. The purpose of this study was to measure Instagram content, consumer purchasing decisions for Visval products on Instagram followers @Visval, and to test the effect of Instagram content for Visval bags on purchasing decisions on Instagram followers @Visval. The theories used in this study are Instagram content theory (Miles 2019: 125-130) and purchasing decision theory (Kotler & Armstrong 2018: 176-177). This study uses a quantitative approach, the method used is the survey method. The population in the study was 161 who were in accordance with the characteristics. The number of samples in this study was 115 respondents, the data collection technique was carried out by distributing questionnaires. Sampling using simple random sampling. The results of this study are that the first Instagram content is quite high with an average value of 3.50 and the second is that the purchasing decision is quite high with an average value of 3.58 and the third is that the influence of Visval bag Instagram content on purchasing decisions has an influence of 58.6%, while the remaining 41.4% is influenced by other factors.